Applications of SPR for the characterization of molecules important in the pathogenesis and treatment of neurodegenerative diseases. (April 2014) - Wittenberg, Nathan J; Wootla, Bharath; Jordan, Luke R; Denic, Aleksandar; Warrington, Arthur E; Oh, Sang-Hyun; Rodriguez, Moses
<x xml:space="preserve">Abstract</x> Characterization of binding kinetics and affinity between a potential drug and its receptor are key steps in the development of new drugs. Among the techniques available to determine binding affinities, surface plasmon resonance has emerged as the gold standard because it can measure binding and dissociation rates in real-time in a label-free fashion. Surface plasmon resonance is now finding applications in the characterization of molecules for treatment of neurodegenerative diseases, characterization of molecules associated with pathogenesis of neurodegenerative diseases and detection of neurodegenerative disease biomarkers. In addition it has been used in the characterization of a new class of natural autoantibodies that have therapeutic potential in a number of neurologic diseases. In this review we will introduce surface plasmon resonance and describe some applications of the technique that pertain to neurodegenerative disorders and their treatment.